THE CONCEPT OF LANGUAGE LEARNING IN BEHAVIORISM PERSPECTIVE - Khoiru Rakhman Abidin (IAIN Salatiga, 2009)
The aims of the study are (1) the concepts of language learning in behaviorism perspective, (2) the relation between language and learning in behaviorism perspective, (3) the influence of behaviorism in language learning. This is a descriptive qualitative study. The results showed that (1) behaviorism theories of languages also give good contribution in language learning process that describes a child can learn language from their environments, (2) behaviorism perspective defines as change of behavior through experience, it means human learn something from their environments, (3) human uses language for communication in the world and he also spreads his culture with his language so human gets knowledge of language through learning.Keywords: Behaviorism; Language; Learning; Language Learning